Evaluation of Salmonella presence in selected United States feed mills. Issue 5 (29th August 2018) - Magossi, Gabriela; Cernicchiaro, Natalia; Dritz, Steve; Houser, Terry; Woodworth, Jason; Jones, Cassandra; Trinetta, Valentina
Abstract: Salmonella is a pathogen of public health concern. Each year, Salmonella infections cost to the food industry approximately $2.3 billion and 33% of the reported cases are associated with beef, poultry, or pork. Pathogen presence in feed mills can represent one of the many potential routes for entry and transmission into the food production chain. Nevertheless, little is known about Salmonella incidence and association with these types of environments. The objective of this study was to investigate Salmonella presence in different feed mills across the United States. Eleven facilities were selected in eight states and 12 sites were sampled within each feed mill. Samples were analyzed following the FSIS guidelines for isolation and identification of Salmonella . Positive isolates were further investigated by a PCR analysis targeting the invA gene to differentiate for Salmonella enterica . The total number of environmental samples collected was 237: 66% resulted culture positive and 13.1% were PCR positive. All sampled feed mills had at least one culture positive site and following production flow the number of positive samples decreased from ingredient receiving to final product. These preliminary results demonstrate the presence of Salmonella in selected United States feed mills and suggest their potential role as vehicle for pathogen transmission and spread into the food production chain. Abstract : Pathogen presence in feed mills can represent one of the many potential routes for entry and transmission into the food production chain. The objective of this study was to investigate Salmonella presence in different feed mills across the United States. Results from this study demonstrate pathogen presence in feed mills and suggest their potential role as vehicle for microbial transmission and spread into the food production chain.